2021
DOI: 10.1017/cjn.2021.4
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Economic Evaluation of Rapid Endovascular Therapy for Acute Ischemic Stroke

Abstract: Background: During the Randomized Assessment of Rapid Endovascular Treatment (EVT) of Ischemic Stroke (ESCAPE) trial, patient-level micro-costing data were collected. We report a cost-effectiveness analysis of EVT, using ESCAPE trial data and Markov simulation, from a universal, single-payer system using a societal perspective over a patient’s lifetime. Methods: Primary data collection alongside the ESCAPE trial provided a 3-month trial-specific, non-model, based cost per quality-adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The finding that EVT is cost-saving is internationally consistent. In Canada, Sevick et al reported that EVT is cost-effective if the time-horizon is 1 year or more, 22 and Xie et al reported a similar benefit using a cost-utility analysis. 23 In the US, by comparing the cost of EVT with the average reimbursement from insurance, Brinjikji et al concluded that the improved patient outcomes associated with EVT may result in decreases in long-term costs.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that EVT is cost-saving is internationally consistent. In Canada, Sevick et al reported that EVT is cost-effective if the time-horizon is 1 year or more, 22 and Xie et al reported a similar benefit using a cost-utility analysis. 23 In the US, by comparing the cost of EVT with the average reimbursement from insurance, Brinjikji et al concluded that the improved patient outcomes associated with EVT may result in decreases in long-term costs.…”
Section: Discussionmentioning
confidence: 99%
“…Model parameters related to efficacy of treatment at 90 days after stroke, [9][10][11][12][13][14][15] health utilities [24][25][26] and costs of care 18,[27][28][29][30][31][32][33][34][35] are summarized in Appendix 1, Supplementary Table S1 at www.cmajopen.ca/content/11/3/E443/suppl/DC1). The descriptions, sources and assumptions for the parameters are also provided in Appendix 1.…”
Section: Model Parametersmentioning
confidence: 99%
“…Incomplete formalized reimbursement services for the mechanical thrombectomy (related to the lack of dedicated procedures) are also a real problem, which, in the case of randomized trials, show that the use of EVT as an option for the treatment of acute ischemic stroke eliminates the costs associated with patient care during the first year of stroke and generates savings in the next years of the patient’s life [ 47 , 48 ]. In the case of staffing problems and the growing number of stroke patients due to the aging society, the solution could be employment standards analogous to those in intensive care units: 1:1 or 1:2.…”
Section: Qualification For the Causal Treatment Of Ischemic Strokementioning
confidence: 99%
“…A particular interesting field about acute stroke management is related to neuroprotective therapies. Some reports suggest a potential role of these therapies [ 137 ], although underlying mechanisms are still unknown and evidence of their usefulness in clinical setting is lacking [ 47 ]. An example of endogenous neuroprotection of damaged neurons after a stroke stimulating the remodeling of the mitochondrial network architecture are the steps of gradual cooling down to 33 °C, which facilitates the transfer of mitochondria from astrocytes to damaged neurons and endothelial cells, while increasing the content of intracellular ATP, mitochondrial membrane potential (MMP), and cell viability during hypoxia [ 138 , 139 ].…”
Section: Examples Of Neuroprotection In the Treatment Of Ischemic Strokementioning
confidence: 99%